Thermal and deformational repairing effect of crushed rock revetment acting as reinforcement along Qinghai–Tibet railway in permafrost regions - Yan-Dong Hou (Advances in Climate Change Research, 2022)
Due to the particularity and complexity of permafrost subgrade, research on its long-term maintenance and reinforcement under climate warming and engineering activities is of great significance. To mitigate subgrade diseases caused by thermal disturbance during the engineering construction and operation in the initial stage, the crushed-rock revetment (CRR) was additionally paved with a thickness of 1.5 m and 1.0 m on some sunny and shady shoulders of the traditional embankments along the Qinghai–Tibet railway, respectively. The improving effects for thermal and deforming stability are evaluated based on observation data of ground temperatures and embankment deformations at two sites from 2002 to 2014. The results show that a larger uplifting magnitude in the artificial permafrost table (APT), greater ground temperature decreasing amplitudes and reduction ranges of settling rate appear under the shady embankment shoulder in warm permafrost region, and both sides in the cold permafrost region when reinforcing with CRR. However, in warm permafrost region, the laying of CRR on the sunny slope of subgrade may cause considerable thermal disturbance to the underlying permafrost foundation, combined with the resulting additional stress, induce the further expansion of differential settlement. Moreover, the thermal stability strengthening effect of the CRR is closely related to the variation of the APT thickness in the earlier stage, convection intensity inside the CRR, ‘cold energy reserve’ in the deeper permafrost, and amount of solar radiation received by the CRR. More effective reinforcements should be implemented to alleviate the potential threaten beneath sunny embankment slope in warm permafrost regions.